Relevansi Nilai Dari Nilai Wajar dan Corporate Governance: Cross Country Analysis - Anda Dwiharyadi (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
This study aims to measure fair value to the relevance and to find the mechanism of corporate governance strengthens the relevance of fair value to stock prices. The results show that the fair value of assets and fair value of liabilities has value relevance at the 5% and 1% confidence levels, respectively. However, the coefficient of fair value of liabilities is negative. If fair value is interacted with corporate governance mechanisms, only the number of board of commissioners meeting frequency that has value relevance is positive. This shows that the number of meetings of the board of commissioners strengthens the value relevance of the fair value of assets. The number of audit committees will weaken the value relevance of the fair value of assets. If the number of members is too large, the audit committee tends to lose focus and participate less. The number of audit committees with financial and accounting backgrounds does not moderate the value relevance of the fair value of assets. Big 4 Audit Office, weakens the value relevance of the fair value presentation of assets. If tested separately, the fair value presentation of both assets and liabilities has no value relevance, either for companies with high or low meeting frequency.